Staging China New Theatres in the Twenty-First Century - Ruru, Li.; SpringerLink (Online service) (New York : Palgrave Macmillan US(Imprint), 2016)
An insightful analysis of more than a dozen Chinese stage productions, Staging China illustrates how Chinese society is reflected by and even constructed through theatre. Scholars from around the globe explore wide-ranging topics including recent approaches to classical theatre, propaganda theatre, and the challenges of independent theatres.
Keywords: Ethnology-Asia.; Theater-History.; Performing Arts; Twentieth-Century Literature